A red-fleshed apple rich in anthocyanins improves endothelial function, reduces inflammation, and modulates the immune system in hypercholesterolemic subjects: the AppleCOR study - Pedret, Anna; Companys, Judit; Calderón-Pérez, Lorena; Llauradó, Elisabet; Pla-Pagà, Laura; Salamanca, Patricia; Sandoval-Ramírez, Berner-Andree; Catalán, Úrsula; Fernández-Castillejo, Sara; Yuste, Silvia; Macià, Alba; Gutiérrez-Tordera, Laia; et al. (Food & function, 2024)
The study determines the sustained and acute effects of a red-fleshed apple (RFA), rich in anthocyanins (ACNs), a white-fleshed apple (WFA) without ACNs, and an infusion from Aronia melanocarpa (AI) with an equivalent content of ACNs as RFA, on different cardiometabolic risk biomarkers in hypercholesterolemic subjects. A randomized, parallel study was performed for 6 weeks and two dose-response studies were performed at the baseline and after intervention. At 6 weeks, RFA consumption improved ischemic reactive hyperemia and decreased C-reactive protein and interleukine-6 compared to WFA consumption. Moreover, at 6 weeks, AI decreased P-selectin compared to WFA and improved the lipid profile. Three products reduced C1q, C4 and Factor B, and RFA and AI reduced C3. Although both RFA and AI have a similar ACN content, RFA, by a matrix effect, induced more improvements in inflammation, whereas AI improved the lipid profile. Anti-inflammatory protein modulation by proteomic reduction of the complement system and immunoglobulins were verified after WFA, AI and RFA consumption. Red-fleshed apples (RFA), improve endothelial function and decrease inflammation. RFA induce more improvements in inflammation than aronia infusion (AI), whereas AI improves lipid profile. RFA, white-fleshed apples and AI modulate immune system.